Analisis Kesalahan Linguistik dalam Pembelajaran Bahasa Arab Berbasis Pedagogi Islam - Muhammad Ibrohim Futuwwatuddin; Moch Mu’izzuddin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study examines linguistic errors in Arabic language learning among students at Daarul Ijabah Jambe Modern Islamic Boarding School by situating the analysis within the framework of Islamic pedagogy. Unlike previous studies that predominantly adopt a technical-descriptive orientation, this research offers a systematic mapping of linguistic errors as a reflective tool to evaluate the effectiveness of Arabic language instruction in the pesantren context. The analysis focuses on five linguistic aspects: phonology, morphology, syntax, discourse, and imlā’ (Arabic orthography). A quantitative descriptive approach was employed, utilizing observation and documentation of students’ spoken utterances and written texts. The findings reveal that linguistic errors are not merely structural in nature such as inaccurate phoneme pronunciation and improper sentence construction but also indicate limited integration between grammatical mastery and communicative learning contexts. These results highlight the need to strengthen Arabic language instruction through pedagogical strategies that integrate linguistic competence with contextual, functional, and communicative principles of Islamic education. Conceptually, this study contributes to the field of Islamic Education by positioning linguistic error analysis as a reflective pedagogical instrument for developing more meaningful and competency-oriented Arabic language learning models in Islamic boarding schools